2013
DOI: 10.1186/1471-2458-13-257
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, betel-nut and cigarette consumption are negatively associated with health promoting behaviors in Taiwan: A cross-sectional study

Abstract: BackgroundOral cancer is the 2nd most common cause of death due to cancer in the south-western coastal region of Taiwan; the standardized mortality of oral cancer is higher than elsewhere in the world. According to the evidence, alcohol, betel-nut and cigarette (ABC) consumption cause oral, nasopharyngeal and related cancers. This study describes the relationships between ABC consumers and health promoting behaviors among community adults living around an area with a high prevalence of oral cancer.MethodsA pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
49
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 19 publications
7
49
0
1
Order By: Relevance
“…The obstacles and delaying tactics faced are also similar 16. To reduce the rate of betel nut consumption, other than through education and health promotion programmes, strategies have been devised to encourage physical activity and oral hygiene 17. Another strategy includes fines and mandatory withdrawal classes for those who spit in public 18.…”
Section: Bioethical Reflectionsmentioning
confidence: 99%
“…The obstacles and delaying tactics faced are also similar 16. To reduce the rate of betel nut consumption, other than through education and health promotion programmes, strategies have been devised to encourage physical activity and oral hygiene 17. Another strategy includes fines and mandatory withdrawal classes for those who spit in public 18.…”
Section: Bioethical Reflectionsmentioning
confidence: 99%
“…In contrast, unhealthy behaviors such as smoking, alcohol consumption, sedentary behavior, long (>9 hr) sleep have been associated with MetS in China (Yu et al, 2014) and Portugal (Santos, Ebrahim, & Barros, 2007). In Taiwan, chewing betel quid (a special kind of nut in Asian countries) (Guo et al, 2013) and unhealthy dietary patterns have also been associated with MetS. Some modifiable lifestyle behaviors, such as smoking and betel quid chewing, have been shown to lead to MetS by decreasing high-density lipoprotein cholesterol levels to promote the development of atherosclerosis (Campbell, Moffatt, & Stamford, 2008) and by promoting adipocyte dysfunction, leading to hyperlipidemia, hyperglycemia, and insulin resistance (Hsu et al, 2010;Slagter et al, 2014;Yu et al, 2014), respectively.…”
mentioning
confidence: 99%
“…Whether these unhealthy behaviors develop into MetS is confounded by age, gender, marriage or living with family, and education (Lim, Nguyen, Choue, & Wang, 2012). Most existing studies have focused on the effects of a single unhealthy behavior on MetS and rarely explored associations among modifiable lifestyle behaviors and MetS (Katano et al, 2010;Lin et al, 2013). The purpose of this study was to examine associations among a cluster of modifiable risky lifestyle behaviors and MetS in Chinese adults in Taiwan.…”
mentioning
confidence: 99%
“…This may give the impression that younger patients were preferentially selected for this report. However, the region from which this study has been reported has a high incidence of betel nut chewing (Adel et al, ; Guo et al, ). As a result, the head and neck cancers are diagnosed at a younger age and recurrences/second primary cancers are not uncommon.…”
Section: Discussionmentioning
confidence: 89%